Trubizh water management paradynamic landscape-technical system - Denysyk, Hryhoriy; Mizina, Sofiia (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2022)
Formulation of the problem. The incorporation of any reclamation system into the existing landscape complexes leads to increased contrast of environments and activation of material-energy-information flows. The construction of the reclamation system in the basin of the Trubizh River radically changed the landscape structure of the riverbed and floodplain, which led to a significant impact on the adjacent landscape complexes. Trubizh water management landscape-technical system goes beyond one river valley, so ill-considered economic activity can lead to deterioration of the ecological condition of adjacent landscape complexes. The study of anthropogenic paradynamic connections between different landscape structures will provide a better understanding of the functioning of the Trubizh water management landscape-technical system and the peculiarities of interaction with adjacent landscapes, which, in turn, will predict its further development and develop ways of rational use. Purpose. The purpose of the article is to study the Trubizh water management landscape-technical system as an anthropogenic paradynamic system. Methods. The process of transformation of natural paradynamic connections into anthropogenic and formation of anthropogenic paradynamic landscape complexes with the help of databases of GIS packages SAS.Planet.Release and GoogleEarthPro is analyzed. The research was conducted using the following methods: system analysis, generalization, comparative-geographical, final results, cartographic, GIS-method. To analyze anthropogenic paradynamic landscape complexes and anthropogenic paradynamic connections between them, GIS packages were used, with the help of databases the process of restructuring of natural paradynamic connections into anthropogenic and formation of anthropogenic paradynamic landscape complexes was analyzed. Results. Because the Trubizh water management landscape-technical system extends beyond one river valley (covering floodplain, floodplain terrace and slope types of areas), it unites the entire river basin into a single whole with the help of anthropogenic paradynamic connections. This poses a threat to the environment, as ill-considered economic activities can lead to the deterioration of the ecological condition of landscape complexes both within one basin and have a negative impact on adjacent basins. Factors in the functioning of paradynamic connections are due to the presence of external and internal links, contrast and spatial dependence between the interacting landscapes complexes. External anthropogenic paradynamic connections include: thermal – the effect of solar radiation on the landscape; mechanical – gravitational influence of watersheds on the low-lying channel-floodplain complex; aquatic – the influence of surface and groundwater on the supply of rivers and the chemical composition of water; social – the impact of economic activity. The internal anthropogenic paradynamic connections include: biocosnic (interaction between living and nonliving matter) and biotic (biocenosis interaction between components). Scientific novelty. The study of paradynamic connections in this complex natural economic structure will provide a better understanding of the features of its functioning and decline, to develop ways of rational use and predict its further development.